Ductile deformation in alumina ceramics under quasi-static to dynamic contact impact - Robert G. Crookes; Benjamin März; Houzheng Wu (Materials & Design, 2020)
Cr3+ Fluorescence spectroscopy and TEM have been used to study the ductile deformation of alumina ceramics underneath an impact contact. The contact was generated by a spherical tungsten carbide indenter under quasi-static, drop weight and ballistic loading conditions. In all circumstances, a ductile deformation region containing dislocations developed below each contact impression. The dislocation density distribution complies with the shear stress distribution predicted by the Hertzian contact model. Ballistic loading resulted in secondary material flow, giving a maximum dislocation density 5–10 times higher than that dictated by the Hertzian contact model. Quantification of dislocation density distribution allowed a critical shear stress for dislocation generation to be estimated. In this alumina ceramic, the critical shear stress is estimated at 2.55 ± 0.10 GPa. Cold work hardening and comminution under dynamic loading are discussed as possible mechanisms for the enhanced dislocation activity under dynamic impact. Keywords: Plastic deformation, Alumina, Dislocations, Impact, Armour, Indentation